2019
DOI: 10.1039/c9cp01482a
|View full text |Cite
|
Sign up to set email alerts
|

The solid phase thermal decomposition and nanocrystal effect of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) via ReaxFF large-scale molecular dynamics simulation

Abstract: The solid phase thermal decomposition and nanocrystal effect are extremely important to understand the ignition, combustion, reaction growth and buildup to detonation under shock wave action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…On the basis of these mechanisms, we have proposed probable reaction channels in parts a and b of Figures that could occur after electronic excitation of RDX. In Figure a, we depict reactions channels that could initiate due to N–NO 2 fission, C–N bond rupture, and HONO-elimination at the ground state of RDX; these reactions have been previously proposed through theoretical calculations ,, and certainly rationalize the products observed in our experiments.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…On the basis of these mechanisms, we have proposed probable reaction channels in parts a and b of Figures that could occur after electronic excitation of RDX. In Figure a, we depict reactions channels that could initiate due to N–NO 2 fission, C–N bond rupture, and HONO-elimination at the ground state of RDX; these reactions have been previously proposed through theoretical calculations ,, and certainly rationalize the products observed in our experiments.…”
Section: Resultssupporting
confidence: 76%
“…Over the past decades, copious studies have been devoted to investigate the fundamental chemical processes involved in the fragmentation of RDX (Scheme ). Diverse methods ranging from shock waves, infrared (IR) lasers, electron beams to ultraviolet (UV) lasers have been employed to initiate the complex dissociation mechanism(s), but the very first reaction step(s) that initialize the decomposition is (are) still debated. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, RMD was also used to simulate the thermal decomposition process of nano-explosives which contain C, H, O and N elements. Zheng et al [25] used the RMD to simulate the whole thermal decomposition process of nanocrystalline RDX. It demonstrated a promising energy distribution mechanism transfer for nanostructure with the information for understanding the effect of the size of nanoparticles on the chemical kinetics of thermal decomposition and reaction growth.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many nanosized metals (Al, Mg, B, W, Zr, Ni, Cu, Fe, Ag, and Co) and metal oxides (e.g., Pb-, Cu-, Bi-, and Fe-based oxides) are widely used in solid propellants as fuels and the burning rate catalysts. , For instance, the nano-CuO and nano-Fe 2 O 3 have better catalytic effects than the microsized ones, , whereas the nano-Al can not only increase the energy content, but also enhance the burn rate of propellants with reduced pressure exponent under high pressure ranges . Furthermore, the thermal decomposition is the initial stage of combustion and explosion of materials, and the performance of thermal decomposition is an essential index that determines the combustion and explosion of materials. Therefore, the thermal behaviors and decomposition mechanisms of ICM-102 under the effects of nanosized metals and metal oxides must be investigated before the ICM-102 is applied in propellants. In this work, the thermal decompositions of ICM-102 and ICM-102 composites (with Al, Co, Mg, Si, Ti, Zr, CuO, and Fe 2 O 3 ) were investigated by thermogravimetric analysis and differential scanning calorimetry (TGA-DSC) technique.…”
Section: Introductionmentioning
confidence: 99%